Infestation of a New Colony of New Zealand White Rabbits housed in a New Animal Facility by Ear Manage Mite, Psoroptes Cuniculi (Journal of Laboratory Animal Science, 2021)
Psoroptes cuniculi is a common ectoparasite that causes ear mite infection in several species including rabbits. Six New  Zealand White rabbits were purchased from a local breeder and were quarantined in a newly established Laboratory  Animal Care Unit (LACU), Faculty of Medicine, Sungai Buloh, Selangor, Malaysia. Clinical examination for endo and  ectoparasites were found to be negative. A prophylactic dose of ivermectin (0.1ml/kg, s.c) was administered. Rabbits were  transferred to a holding area after 30 days of quarantine. Routine husbandry practices were followed under the guidance  of a trained research assistant (RA). Approximately after 2-3 weeks, hard and scaly skin lesions were observed in the fore  paws and hairy portion of the nails in three rabbits. In addition, both ears were observed to exhibit severe otitis externa  with heavy crusting. The present study attempts to investigate the mode of transmission and the preventive measures to  be adopted. Ear and fore paw scrapping were mixed with liquid paraffin and subjected to light microscopic (10 & 40X)  observation. Psoroptic mites were observed and identified as Psoroptes cuniculi. Six rabbits were treated initially with  ivermectin (0.2 ml/kg, s.c) and 0.4ml was instilled into both the ears. The treatment was repeated similarly after two weeks.  It was identified that the transmission of P.cuniculi was through the RA. The RA has been visiting the rabbit breeder to  learn the basic techniques of handling rabbits. The same lab coat was used by the RA at rabbit breeder facility and LACU.  Transmission of P.cuniculi may be from the breeder through RA clothing. Veterinarians or animal care takers should follow  the standard operating procedures for laboratory animal husbandry. Disposable personal protective equipment’s should be  practiced during routine husbandry practices.
Keywords: Rabbits; Ectoparasites; Psoroptic mites; Psoroptes cuniculi; Ivermectin; Psoroptic scabies; Psoroptic mange